Blockchain in the Global Trade Ecosystem: Efficiency, Transparency, and Security - Hartono, Margareta Kristiani (Universitas Ibn Khaldun Bogor, 2025)
Blockchain is an innovative technology that has the potential to revolutionize the global trade ecosystem by providing unprecedented efficiency, transparency, and security. This article examines the role of blockchain in addressing the main challenges of international trade, such as complex bureaucracy, fraud risks, and lack of data visibility. Blockchain enables decentralized, permanent, and immutable data recording, thereby creating a more secure and trustworthy system. Through the implementation of smart contracts, this technology simplifies administrative processes such as export-import documentation, customs, and cross-border payments, ultimately reducing operational costs and speeding up transactions. Additionally, blockchain provides real-time product tracking from producers to end consumers, ensuring product authenticity and compliance with ethical and sustainability standards. However, despite offering significant benefits, the adoption of blockchain in global trade faces challenges such as non-uniform regulations, scalability limitations of the technology, and the need for high initial investment. This article not only identifies the potential of blockchain in enhancing international trade efficiency but also provides strategic recommendations to overcome these barriers. With proper implementation, blockchain can serve as a catalyst for transforming global trade into a more inclusive and sustainable system